Balance ability and all-cause death in middle-aged and older adults: A prospective cohort study - Xie, Kaihong; Han, Xiao; Hu, Xuanhan (Frontiers in Public Health, 2023)
Objective The present study aimed to explore the relationship between balance ability and all-cause death in middle-aged and elderly people and to provide a basis for formulating a balanced training plan for middle-aged and older people in China. Methods Based on data from the China Health and Retirement Longitudinal Study (CHARLS) carried out in the years 2011, 2013, 2015, and 2018, 18,888 participants aged 45 years and above were included. Cox proportional hazard models were designed to evaluate the effect of balance ability on death events. Results The present study found that there was an association between balance ability and death among middle-aged and older people. Multivariate Cox proportional hazard regression model analysis showed that the risk of death decreased by 10% (HR = 0.90,95% CI: 0.85–0.95) for every second increase in balance ability. With balance ability <10 s as the reference group, the adjusted HRs were 0.61 (0.44–0.85) among middle-aged and elderly people. The death density of balance ability of <10 s was 73.87 per thousand person-years higher than that of ≥10 s. There was no interaction between balance ability and chronic disease, overweight, and obesity (P > 0.05). Conclusion The risk of all-cause death in middle-aged and older people increased with the decrease in balance ability and showed no statistical significance between chronic disease, overweight, and obesity, as corroborated by the present study.